Genetic Toolkits to Design and Build Mammalian Synthetic Systems. Issue 10 (October 2021) - Di Blasi, Roberto; Zouein, Annalise; Ellis, Tom; Ceroni, Francesca
Abstract : Construction of DNA-encoded programs is central to synthetic biology and the chosen method often determines the time required to design and build constructs for testing. Here, we describe and summarise key features of the available toolkits for DNA construction for mammalian cells. We compare the different cloning strategies based on their complexity and the time needed to generate constructs of different sizes, and we reflect on why Golden Gate toolkits now dominate due to their modular design. We look forward to future advances, including accessory packs for cloning toolkits that can facilitate editing, orthogonality, advanced regulation, and integration into synthetic chromosome construction. Highlights: Synthetic biology benefits from standardisation. The development of the field relies on simple, cheap, and high-throughput methods that improve the design–build–test cycle. The development of high-throughput cloning methods has paved the way to the emergence of many cloning toolkits, providing a wealth of standardised parts that can be easily assembled, thus speeding up the engineering of complex genetic devices. Although cloning toolkits for mammalian synthetic biology are underrepresented compared to their bacterial and yeast counterparts, some are now made available to the community.